Contribution to the Study of Septal - Pospisil Siegrich, Luisa (1965)
The study Septal is important, given the high incidence in our country of that disease (48%), as shown in a previous study (1). The ventricular septal defect was first described in 1879 by Roger Henry on "Academie Francaise" (2). Twelve ai10S later found in Von Dupré necropsy, the existence of a ventricular septal defect. Dalrymple was the first who described a high ventricular septal defect in the membranous portion. H. Taussig (3) based on their own study, contributed to the clinical description of this malformation in 1947. The first successful operations were carried out by Warden and Lillehei in 1956; and Peru was operated for the first time this defect in 1962 in the Department of Cardiology at Children's Hospital.